Non hepato-renal abdominal hydatid disease - Rebollo dos Santos, Juan N; Varalla, Mary; Terra, Eneas; di Leoni, Francisco; Campos, Néstor; Geninazzi, Héctor; Lozano, Winston (Cirugía del Uruguay, 1985)
Non hepato-renal abdominal hydatid di sea se is analyzed. lts important incidence in the rural social a ea is pointed·out; the same has remained unchanged o e last thirty years.